Can the cycle threshold (Ct) value of RT-PCR test for SARS CoV2 predict infectivity among close contacts?. Issue 9 (September 2021) - Al Bayat, Soha; Mundodan, Jesha; Hasnain, Samina; Sallam, Mohamed; Khogali, Hayat; Ali, Dina; Alateeg, Saif; Osama, Mohamed; Elberdiny, Aiman; Al-Romaihi, Hamad; Al-Thani, Mohammed Hamad J.
Abstract: Background: COVID-19 global pandemic is an unprecedented health emergency. Rapid identification and isolation of infected individuals is crucial. Qatar's National Health Strategic Command Group adopted a cut off 30 for Ct value of RT-PCR result of a positive case to decide on duration of isolation and quarantine period for their close contacts. Aim: To test if Ct value cut off 30 reflects on the infectivity potential among close contacts. Methodology: All positive cases reported during July' 2020 whose contacts had been traced and swabbed were extracted from database after removing personal identifiers. Close-contact was defined as anybody who has been within 2 m distance of a confirmed positive case for 15 min or more, without any personal protection equipment. Descriptive analysis was done and test of significance of difference in positivity among the contacts of those with ct < 30 and >30 was done. Results: 2308 COVID-19 positive cases were followed up. More than three-quarters had a Ct value < 30, with a mean Ct value of 24.05(+6.48). On an average 6 contacts were swabbed per case. More than half the positive cases followed up had at least one secondary case, with median positivity rate 12.5%. A significant relation was noted between Ct value cut-off 30 and secondary transmission (1.5 times more risk among those with Ct value < 30). A significant difference was noted in median positivity rate between close contacts of positive cases with Ct value > 30 or <30. Conclusion: Further studies combining PCR assays, culture studies and contact tracing are needed to define which factors can be used to reliably predict the infectious status of patients with COVID-19.